2010
DOI: 10.1029/2009jd013489
|View full text |Cite
|
Sign up to set email alerts
|

A 10 year climatology of Arctic cloud fraction and radiative forcing at Barrow, Alaska

Abstract: A 10 year record of Arctic cloud fraction and radiative forcing has been generated using data collected at the Atmospheric Radiation Measurement (ARM) North Slope of Alaska site and the nearby NOAA Barrow Observatory (BRW) from June 1998 to May 2008. The cloud fractions (CFs) derived from ARM radar‐lidar and ceilometer measurements increase significantly from March to May (0.57→0.84), remain relatively high (∼0.80–0.9) from May to October, and then decrease from November to the following March (0.8→0.57), havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
158
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 163 publications
(184 citation statements)
references
References 48 publications
18
158
2
Order By: Relevance
“…The surface LWnet and SWnet fluxes were respectively 9.8 and 4.2 Wm -2 higher and lower than their corresponding climatic means, resulting in a 5.6 Wm -2 positive anomaly of net radiative flux (more downward). This result is consistent with previous findings (Francis et al 2005;Dong et al 2010) where both studies provide strong support for the finding in this study, i.e., LW effect overwhelmed SW effect over the AOF. For example, Francis et al (2005) studied the ice edges of all six peripheral seas over Arctic and found that the LW anomalies contributed about 40 % to the total variability, but the SW anomalies were overwhelmed by the LW impact when CF was high.…”
Section: Results and Discussion: Inter-annual And Seasonal Variationssupporting
confidence: 83%
See 1 more Smart Citation
“…The surface LWnet and SWnet fluxes were respectively 9.8 and 4.2 Wm -2 higher and lower than their corresponding climatic means, resulting in a 5.6 Wm -2 positive anomaly of net radiative flux (more downward). This result is consistent with previous findings (Francis et al 2005;Dong et al 2010) where both studies provide strong support for the finding in this study, i.e., LW effect overwhelmed SW effect over the AOF. For example, Francis et al (2005) studied the ice edges of all six peripheral seas over Arctic and found that the LW anomalies contributed about 40 % to the total variability, but the SW anomalies were overwhelmed by the LW impact when CF was high.…”
Section: Results and Discussion: Inter-annual And Seasonal Variationssupporting
confidence: 83%
“…This simple parameterization may generate considerable biases in upwelling and downwelling SW fluxes, which lead to problems in the evaluation of the icealbedo feedback process. The observed snow/ice albedos at the BSRN Barrow site (Zib et al 2012, Dong et al 2010 and during the Surface Heat Budget of the Arctic Ocean (SHEBA) experiment (Intrieri et al 2002) are around 0.80-0.90. The downwelling SW flux is primarily determined by the following three parameters: cloud fraction and optical depth, and surface albedo.…”
Section: Assessment Of Merra Reanalysismentioning
confidence: 99%
“…seasonal variation of total cloud occurrence [Intrieri et al, 2002;Dong et al, 2010;Shupe et al, 2011;Shupe, 2011] with lower magnitudes.…”
Section: 1002/2014jd023022mentioning
confidence: 99%
“…Radiation data from the US Department of Energy Atmospheric Radiation Monitoring and the NOAA Global Monitoring Division observatories in Barrow, Alaska, were obtained and processed at the University of North Dakota (Dong et al 2010). These data were used, in combination with ice concentration, to estimate the long-term change in energy absorbed by the surface ocean, following Perovich et al (2007).…”
Section: Satellite Imagerymentioning
confidence: 99%